2018
DOI: 10.1177/0954411917752026
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mesh refinement for elastic modulus reconstruction in elastography

Abstract: Meshes play a crucial role in determining the accuracy of the elastic modulus reconstruction in the elastography when the finite element method is employed. In this article, we propose an adaptive mesh refinement strategy which can ensure the coincidence of the meshes with the shape of the inclusions in the observed tissue. This strategy is based on the intensity distribution of the strain image where the variance of the strain distribution in each element of the meshes is used to measure the homogeneity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…By recursively calculating eqn (10) and (11), we can get the admittance of the first interface after the admittance recursion method:…”
Section: (G) and (H)mentioning
confidence: 99%
See 1 more Smart Citation
“…By recursively calculating eqn (10) and (11), we can get the admittance of the first interface after the admittance recursion method:…”
Section: (G) and (H)mentioning
confidence: 99%
“…Antireflective coatings [11][12][13][14] play an indispensable role in today's optical field and have been widely used in various types of optical equipment. In terms of light reflection suppression, the C-Si solar cell with the AR film designed by Tang et al 3 showed excellent broadband suppression of surface light reflectance of 17.7%.…”
Section: Introductionmentioning
confidence: 99%
“…The active system, compared to the passive system, is characterized by a much higher efficiency, unfortunately, it is accompanied by the noise produced by the fans, which can be annoying in terms of working comfort. [7,8] Liquid cooling [9,10] is an indirect cooling system, which somewhat resembles the system used in automobiles. It consists primarily of a water block, water pump, radiator and the appropriate thickness of hoses.…”
Section: Introductionmentioning
confidence: 99%